1994
DOI: 10.1063/1.358498
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical calculation of longitudinal-optical-phonon lifetime in GaAs

Abstract: The anharmonic decay of longitudinal-optical (LO) phonons in zinc-blende semiconductors has been studied. Based on an approach in which the anharmonic crystal potential is estimated using the theory of elasticity, the lifetime of LO phonons via emission of two acoustic phonons is calculated as a function of lattice temperature and phonon wave vector. Application of this model to bulk GaAs shows an excellent agreement with available experimental data. Since the parameters employed in the model can be obtained e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 13 publications
3
29
0
Order By: Relevance
“…On the other hand, away from the TO-phonon frequency the permittivity, obviously, depends only weakly on damping under the condition (ω) ω, that makes it possible to use (1) with T = const. In the work [34] (using the elastic theory for the anharmonic potential of the crystal), the lifetime of bulk LO-phonons is calculated as a function of both temperature and wavevector. Considering only the channel of the LO-vibration relaxation (the anharmonic decay into two acoustic phonons), the authors found that the wavevector dependence of the TO-phonon lifetime is weak.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, away from the TO-phonon frequency the permittivity, obviously, depends only weakly on damping under the condition (ω) ω, that makes it possible to use (1) with T = const. In the work [34] (using the elastic theory for the anharmonic potential of the crystal), the lifetime of bulk LO-phonons is calculated as a function of both temperature and wavevector. Considering only the channel of the LO-vibration relaxation (the anharmonic decay into two acoustic phonons), the authors found that the wavevector dependence of the TO-phonon lifetime is weak.…”
Section: Discussionmentioning
confidence: 99%
“…Self-energies due to these interactions are both modeled within the self-consistent Born approximation. The anharmonic decay of LO phonons, which is known to be important for a proper description of the relaxation processes in QDs, is also taken into account by adding a finite linewidth (corresponding to the lifetime of 5 ps, which is within the range of lifetimes reported in [16]) to the Green's functions of free phonons. A system of algebraic equations (for the retarded Green's functions , the lesser Green's functions , and the self-energies and ) containing the Dyson equation, the Keldysh relation, and the expressions for self-energies [11], [17] is then solved self-consistently.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The transition rate from the initial state with an electron in state and LO-phonons with the wave vector (where takes all possible values of the phonon wave vector) to the final state with an electron in state and one more (less) phonon with the wave vector is given by [10] (9) where electron-LOphonon coupling strength, where (10) is the LO-phonon energy and is the inverse LO-phonon lifetime due to its decay into two LA-phonons. Since is weakly dependent on the phonon wave vector [28], this dependence was neglected. As it is thought that the influence of phonon confinement on scattering rates is not so important in AlGaAs-GaAs and InGaAs-GaAs nanostructures [29], we have assumed bulk GaAs LO-phonon modes and correspondingly the Frölich interaction Hamiltonian is given by (11) where and are the phonon annihilation and creation operators and (12) with and being high frequency and static dielectric constants, respectively.…”
Section: ) Interaction With Lo Phononsmentioning
confidence: 99%
“…It was assumed that the doping density is such that the dots are occupied with electrons on average, as already mentioned. The material parameters for the calculation of the energy levels were taken from [35], the parameters for the calculation of transition rates due to interaction with phonons were taken from [36] and the temperature dependence of LO-phonon lifetime is taken from [28]. The energy level scheme of the dot considered is presented in Fig.…”
Section: A Active Regionmentioning
confidence: 99%